Antecedents of consumers’ intention and behavior to purchase organic food in the Portuguese context - Ferreira, Sandra (2023)
The demand and commercialization of organic foods is developing rapidly. However, there is an imbalance between the increasing use of these products and the limited attention of researchers to this category of products. The present study intends to evaluate the antecedents of the consumer purchase intention and behavior on organic foods, based on the Theory of Planned Behavior (TPB). To reach the research objectives, a quantitative methodology was developed. An online questionnaire was applied in organic food social network groups and Portuguese organic food stores. To test the hypothesis, structural equation modelling (SEM) was conducted. Findings revealed that environmental concern has a significantly positive effect on purchasing attitude and on purchase intention. Health consciousness has a significant and positive relationship with attitude and purchase intention, and attitude has a significant and positive relationship with purchase intention. Finally, purchase intention has a significant and positive relationship with purchase behavior. Theoretically, this study is a response to frequent requests to investigate beyond consumer intention and assess influences on actual behavior. Producers and marketing professionals may utilize our findings to develop strategies to attract the growing organic food community and encourage its purchase.